Interrelating digital strategy, operational effectiveness, and innovation outcomes in colombian organizations (2024)
This thesis explores the relationships between digital strategies, innovation outcomes, and operational effectiveness in companies operating in Colombia. The study addresses Colombia's decline in global competitiveness and argues that adopting digital strategies, particularly those aligned with Industry 4.0, can improve productivity, flexibility, and competitiveness. It highlights how digital transformation can enhance operational effectiveness through the integration of innovative technologies, such as big data and artificial intelligence, into business processes. These strategies not only streamline operations but also enable firms to explore new business models and optimize customer experiences. The research employed Structural Equation Modeling (SEM) to investigate the relationships between digital strategy, innovation, and operational effectiveness, gathering data from 141 respondents in management roles within large colombian organizations. The findings suggest that innovation is a key mediator between digital strategies and operational effectiveness. While a direct link between digital strategies and operational success was not found, the study confirms that innovation outcomes have a significant positive impact on operational effectiveness. The thesis emphasizes that companies should focus on aligning their digital strategies with innovation to enhance competitiveness and achieve long-term operational improvements.